Front-Page Coverage of the First Day of the Russian Invasion on Ukraine in 2022. The Ethnographic Discourse Analysis Based on the Polish Press Reportage - Strukowska, Marta E. (2022)
This article explores the discursive patterns of communicative events during the Russia-Ukraine war in 2022.Studied through an ethnographic discourse analysis lens (e.g., Hymes 1972b, Saville-Troike [1982] 2003), Polishfront-page news articles are shown to be artefact-filled language environment anchored in culture (Duranti[1997] 1999, Hoijer 1953) that can be studied by means of communicational grammar (Chruszczewski 2002)consisting of well-entrenched conceptualisations in the form of keywords and collocations as concomitantsof cultural scripts (Goddard and Wierzbicka 2014, Baker 2006, Wierzbicka 1997). It agues that legitimation ofpatterned representations is based on a three-fold conceptual typology: (1) the axiological (valuational) dimension(Romanyshyn 2020, Pomeroy 2004, Krzeszowski 1997), (2) the metaphorical account of spatial/territorialreference (proximization) (Cap 2013), (3) us vs. them dichotomy (Van Dijk 1992a). It demonstrates how Polishpress manufactures and discursively creates ideological attachments which underlie Poland’s cultural legacy.
Keywords: anthropolinguistics; ethnographic discourse analysis; Russia-Ukraine war; cultural scripts